PENGARUH CORPORATE GOVERNANCE, KEPEMILIKAN MANAJERIAL DAN CASH HOLDINGS TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Perbankan Konvensional yang Terdaftar di BEI Tahun 2014-2018) - Gaby Laura Dwi Putri Tindaon; Abdul Rohman (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to examine the effect of corporate governance, managerial ownership, and cash holdings on firm value in conventional banking firms. Variables used in this examination are size of the board of commissioners, independent commissioners, auditor’s reputation, managerial ownership, and cash holdings as the independent variables, also firm value as the dependent variable. This research used banking subsector during the 2014 – 2018 with total sample is 190 sample. Sampling based on purposive sampling method that follows certain criteria(s). Multiple regression analysis with OLS approach is the analysis method used in this research.The results of this study indicates that independent commissioners have a positive and significant effect on firm value. Beside that, managerial ownership has a positive and insignificant effect on firm value. Size of the board of commissioners and cash holdings have a negative and insignificant effect on firm value. Auditor’s reputation has a negative and significant effect on firm value.